2016
DOI: 10.1158/2326-6066.cir-16-0128
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic HPV Cancer Vaccine Targeted to CD40 Elicits Effective CD8+ T-cell Immunity

Abstract: Human papillomavirus (HPV), particularly HPV16 and HPV18, can cause cancers in diverse anatomical sites, including the anogenital and oropharyngeal (throat) regions. Therefore, development of safe and clinically effective therapeutic vaccines is an important goal. Herein, we show that a recombinant fusion protein of a humanized antibody to CD40 fused to HPV16.E6/7 (aCD40-HPV16.E6/7) can evoke HPV16.E6/7-specific CD8 þ and CD4 þ T-cell responses in head-and-neck cancer patients in vitro and in human CD40 transg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…In our recent studies [29,30] , we have further demonstrated the proof of concept that strongly support the clinical development of CD40-targeting therapeutic vaccines for HPV16-associated cancers using our prototype vaccine, anti-CD40-HPV16.E6/7 protein.…”
Section: Research Highlightmentioning
confidence: 57%
See 4 more Smart Citations
“…In our recent studies [29,30] , we have further demonstrated the proof of concept that strongly support the clinical development of CD40-targeting therapeutic vaccines for HPV16-associated cancers using our prototype vaccine, anti-CD40-HPV16.E6/7 protein.…”
Section: Research Highlightmentioning
confidence: 57%
“…Critical findings in our recent study [30] with a prototype vaccine for HPV16-associated malignancies, anti-CD40-HPV16.E6/7, include that it can evoke HPV16.E6/7-specific CD8 + and CD4 + T cell responses in head-and-neck cancer patients in vitro and in human CD40 transgenic (hCD40tg) mice in vivo. The combination of anti-CD40-HPV16.E6/7 and poly(I:C) efficiently primed HPV16.E6/7-specific T cells, particularly CD8 + T cells, in hCD40tg mice and could thus mount therapeutic immunity against challenged tumors.…”
Section: Malignant Transformation Of Hpv-infected Cells Is Drivenmentioning
confidence: 89%
See 3 more Smart Citations